1986
DOI: 10.1093/oxfordjournals.aje.a114470
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Certification of Deaths Due to Asthma

Abstract: In a two-year study of asthma mortality in New Zealand conducted between August 1981 and July 1983, the certified cause of death and its subsequent statistical coding was compared with the opinion of a panel of respiratory physicians who had made detailed enquiry into the medical history and circumstances surrounding the death of each patient. When the panel's opinion was taken as the reference standard, the national health statistics overestimated asthma mortality for all age groups by 26.0%. For patients age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
1
5

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(38 citation statements)
references
References 0 publications
1
31
1
5
Order By: Relevance
“…This corresponds with previous descriptions in comparable studies [5,8,9,17]. Unexpectedly, the authors identified 3% false negative asthma deaths wrongly coded to another cause, and 9% false negative asthma deaths coded under adjacent respiratory codes.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…This corresponds with previous descriptions in comparable studies [5,8,9,17]. Unexpectedly, the authors identified 3% false negative asthma deaths wrongly coded to another cause, and 9% false negative asthma deaths coded under adjacent respiratory codes.…”
supporting
confidence: 89%
“…The authors were surprised when the current data were compared with other published investigations into the same age group [5,9]. There was no indication of an overestimation of asthma death in the present study.…”
contrasting
confidence: 81%
See 1 more Smart Citation
“…As DOs com menção de asma não apresentam dificuldades para a transformação das causas de morte em códigos da CID-10. Verifica-se que o trabalho do codificador é acurado e não se constitui em fonte de erro que comprometa a qualidade das estatísticas de mortalidade 25,26,27,28 . A tarefa subseqüente da identificação da causa básica de morte por meio da aplicação das regras sobre mortalidade da OMS 7 é realizada automaticamente e de modo uniforme, fato que elimina a decisão subjetiva da seleção manual e acompanha padrões internacionais 20,21,28 .…”
Section: Methodsunclassified
“…A tarefa subseqüente da identificação da causa básica de morte por meio da aplicação das regras sobre mortalidade da OMS 7 é realizada automaticamente e de modo uniforme, fato que elimina a decisão subjetiva da seleção manual e acompanha padrões internacionais 20,21,28 . Conclui-se que o problema maior ocorre na etapa anterior, qual seja, a do preenchimento da DO pelos médicos 26,27 . Nessa etapa se concentra o maior número de estudos.…”
Section: Methodsunclassified